O impacto de anúncios econômicos no mercado futuro brasileiro de aç\~oes, juros e câmbio - Francisco Eduardo de Luna e Almeida Santos; Márcio Gomes Pinto Garcia; Marcelo C. Medeiros (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– In this paper, the relationship between macroeconomic fundamentals and asset prices is explored by estimating the impact of macroeconomic announcements in the Brazilian futures market. Using intraday data from October 2008 to January 2011, results show that external macroeconomic announcements dominate price changes in the Foreign Exchange and Ibovespa futures markets, while the impact of the domestic ones is mainly restricted to Interest Rate futures contracts. There is also evidence that price reactions are conditional on the state of the economy.
Keywords: E44; F31; G14; 330; high frequency data; macroeconomic announcements; financial markets